KONTRIBUSI ILMUWAN MUSLIM TERHADAP PERKEMBANGAN EKONOMI - Mismiwati, Mismiwati (Universitas Islam Negeri Raden Fatah Palembang, 2016)
Nowadays, most of the Islamic world is still relatively underdeveloped developing countries even seen from the size and criteria of wealth, employment, education and health. A fact that is contrary to the doctrine, values and norms of Islam itself. The importance of building Islamic economic thought is based, two arguments, first, theological arguments which claim that Islam is a heavenly religions based on revelation (Quran) that serves to guide the life of humanity, whether social, political, and economic. First, the empirical philosophical arguments and factual. Second, there is a gap and a dearth of literature in the field of economic science to explain the philosophy, institutions, principles, values, norms and laws of Islamic economics; second, the fact shows the need for the economic development of Islamic countries. ملخص :في الوقت الحاضر، فإن معظم العالم الإسلامي لا يزال البلدان النامية المتخلفة نسبيا حتى يتضح من حجم ومعايير الثروة والعمل والتعليم والصحة. وحقيقة أنه لا يتعارض مع العقيدة والقيم وقواعد الإسلام نفسه. ويستند على أهمية بناء الفكر الاقتصادي الإسلامي، حجتين، الأولى، والحجج اللاهوتية التي تدعي أن الإسلام هو الديانات السماوية على أساس الوحي (القرآن) الذي يعمل على توجيه الحياة الإنسانية، سواء كانت اجتماعية أو سياسية، واقتصادية. وثانيا، فإن الحجج الفلسفية والواقعية التجريبية. أولا، هناك فجوة وقلة الأدب في مجال العلوم الاقتصادية لشرح فلسفة والمؤسسات والمبادئ والقيم والأعراف والقوانين الاقتصاد الإسلامي. الثانية، يظهر حقيقة الحاجة إلى التنمية الاقتصادية للبلدان الإسلامية.